Effects of carbon supporter on oxygen reduction reaction catalytic activity in proton exchange membrane fuel cell of bimetallic Pt-Ni nanoparticles electrocatalysts - L. Payattikul (2020)
© 2020 Institute of Physics Publishing. All rights reserved. Platinum nanoparticles supported on carbon black (Pt/C) are widely used as the electrocatalysts for oxygen reduction reaction (ORR) in proton exchange membrane fuel cells (PEMFCs). Nevertheless, the kinetics of the ORR or rate of reaction is relatively slow. Recently, researchers theoretically report that, the bimetallic platinum-nickel supported on carbon black (Pt-Ni/C) have extremely high ORR activities. Therefore, this work aims to synthesize Pt-Ni/C nanoparticles electrocatalysts for ORR via solid-state chemistry method (gas phase synthesis), which involved impregnation of metal precursors on supported carbon and reducing them in an environment of carbon monoxide (CO) and hydrogen (H2) gases mixture. The Pt-Ni nanoparticles were prepared with different carbon (i.e. Graphene, Vulcan XC-72R and Ketjen black). The ORR activities and durability of these electrocatalysts were examined by voltammetry technique, which consisted of cyclic voltammetry (CV) and linear sweep voltammetry (LSV) under acidic condition. The results demonstrated that different types of carbon supporters could affect the ORR catalytic activities. Pt-Ni nanoparticles supported on ketjen black (Pt-Ni/K) had the highest ORR activities for both specific activity (SA) and mass activity (MA). Furthermore, after 4,000 voltage cycles of the accelerated durability test (ADT), the Pt-Ni/Ketjen black still showed better ORR stability than Pt-Ni/Vulcan XC-72R and Pt-Ni/Graphene, respectively.